18F-FDG super bone marrow uptake: A highly potent indicator for the malignant infiltration. Issue 52 (December 2016) - Alam, Mohammed Shah; Fu, Lilan; Ren, Yun-Yan; Wu, Hu-Bing; Wang, Quan-Shi; Han, Yan-Jiang; Zhou, Wen-Lan; Li, Hong-Sheng; Wang, Zhen
Abstract : Abstract: The present study was performed to investigate whether the markedly 2-deoxy-2-(fluorine-18) fluoro-D-glucose ( 18 F-FDG) uptake in the bone marrow (BM) is a presentation of malignant infiltration (MI). Super bone marrow uptake (super BMU) was used to name the markedly 18 F-FDG uptake on BM, which was similar to or higher than that of the brain. From April 2008 to December 2015, 31 patients with such presentation were retrospectively reviewed. The 18 F-FDG uptake was semiquantified using SUVmax and BM to cerebellum (BM/C) ratio. The origin of super BMU was diagnosed by pathology. Some blood parameters, as well as fever, were also collected and analyzed. For comparison, 106 patients with mildly and moderately uptake in BM and 20 healthy subjects were selected as the control group. Bone marrow MI was diagnosed in 93.5% (29/31) patients with super BMU, which mostly originated from acute leukemia and highly aggressive lymphoma. The super BMU group had markedly higher 18 F-FDG uptake in the BM than those of mildly and moderately uptake, and the control subjects (all P  = 0.000) and the BM/C ratio reached a high of 1.24 ± 0.36. The incidence of bone marrow MI in the super BMU group was markedly higher than that of mildly and moderately uptake (93.5% vs 36.8%, P  = 0.000). Based on the receiver operating characteristic analysis, when cut-off values of BM/C and SUVmax were set at 0.835 and 6.560, the diagnostic specificity for bone marrow MI reached the high levels of 91.4% and 95.7%, respectively. In 15 patients with bone marrow MI, the extra-BM malignant lesions were simultaneously detected by 18 F-FDG PET/CT. The liver and the nasal cavity involvements were only found in the patients with lymphoma, but not in those with leukemia. A decrease of leukocyte, hemoglobin, and platelet counts was noted in 48.4%, 86.2%, and 51.5% of patients with bone marrow MI, respectively. The present study revealed that super BMU was a highly potent indicator for the bone marrow MI.